General Henri Gouraud speaks to students at the MacJannet Elms school, 1939 (Tufts Archival Research Center, 2005)
6 x 8, Description on photo: "General Henri Gouraud (who had the Rainbow Division under his command, and retired as Military Govenor of Paris in 1938) presenting his library of autographed volumes written by American authors to the MacJannet Schools." Donald MacJannet is seated figure to the left of the American flag.